The impact of globalization on the oriental languages, education and culture (Journal of Oriental Studies, 2020)
This article focuses on oriental languages such as Arabic, Hindi, Bengali, and Japanese. The author pays great attention to the functionality of these languages in different countries: in particular, in Egypt, India, Bangladesh and Japan. The main goal of the study is to analyze materials related to the position of these languages in the world, to identify phenomena that reveal some changes in language and culture. Due to changes in the language system, due to the globalization process taking place throughout the world, English retains the status of the most important language of international communication. After analyzing the linguistic situation in these countries, the author believes that globalization has a serious impact on national education systems. The main languages of instruction in many countries are the state language of the country and English. The author points out the problems of national schools, such as the danger of lack of achievements in national education, the unification of educational systems of eastern states. Key words: language , language system, education, culture, globalization.